STUDI KEMAMPUAN GURU KIMIA SMA LULUSAN UNY DALAM MENGEMBANGKAN SOAL UAS BERBASIS HOTS - Iskandar, Dodi; Senam, Senam (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2015)
This study aimed to investigate senior high school chemistry teachers ability to develop semester examination materials based on higher-order thinking skills. This kind of research was a survey. A number of respondents were 15 chemistry teachers with 559 questions of semester final examination in year 2013. The used methods was documentation. This research used a document check list as an instrument to collect data. The analyzed data were C1 (remember), C2 (understand), C3 (apply) that included lower order thinking skills (LOTS), C4 (analyze), C5 (evaluate) and C6 (create) which classified to higher order thingking skills (HOTS). The results of the study was senior high school chemistry teachers ability to develop a semester examination material based on higher order thinking skills is 13,9%, which consists of C4 13.2%; C5 0.7% and C6 0.0%.